2021
DOI: 10.1371/journal.pone.0252220
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-13 rs1800925/-1112C/T promoter single nucleotide polymorphism variant linked to anti-schistosomiasis in adult males in Murehwa District, Zimbabwe

Abstract: Background Chronic schistosomiasis is predominantly induced through up-regulation of inflammatory cytokines such as interleukin (IL)-13. IL-13 may contribute to the disease outcomes by increasing eosinophil infiltration thereby promoting fibrosis. IL-13 may act as an immunosuppressive inflammatory cytokine that may promote carcinogenesis and also may offer protection against schistosomiasis thereby reducing risk of schistosome infections. Our study evaluated the frequency of the IL-13 rs1800925/-1112 C/ T prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Diverse findings have been reported by different research groups studying the SNV rs1800925 in the promoter region (−1112 C/T) and its association with IL-13 levels. One study observed an association between high levels of IL-13 and the CC genotypes in schistosomiasis-uninfected individuals in Zimbabwe ( 60 ), while another study indicated that TT genotypes are correlated with high IL-13 levels in S. japonicum -infected individuals ( 61 ). Another SNV rs2069739A>G, an intron variant of IL13, has also been linked with plasma levels of IL-13.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diverse findings have been reported by different research groups studying the SNV rs1800925 in the promoter region (−1112 C/T) and its association with IL-13 levels. One study observed an association between high levels of IL-13 and the CC genotypes in schistosomiasis-uninfected individuals in Zimbabwe ( 60 ), while another study indicated that TT genotypes are correlated with high IL-13 levels in S. japonicum -infected individuals ( 61 ). Another SNV rs2069739A>G, an intron variant of IL13, has also been linked with plasma levels of IL-13.…”
Section: Discussionmentioning
confidence: 99%
“…Another SNV rs2069739A>G, an intron variant of IL13, has also been linked with plasma levels of IL-13. Carriers of the allele A of SNV rs2069739 are associated with an increased risk of having low plasma concentrations of IL-13 ( 30 , 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies have revealed associations between SNPs in genes encoding cytokines and TFs and susceptibility to schistosomiasis, including in STAT6 , IL4 , IL5 , IL10 , and IL13 [ 15 21 ]. Recently, Choto and colleagues identified an association between IL13 rs1800925 and elevated IL-13 concentrations in schistosome-uninfected but not schistosome-infected individuals in Zimbabwe [ 22 ]. In addition, Marume and colleagues identified an association between IL10 SNP rs1800871, protection from S .…”
Section: Introductionmentioning
confidence: 99%